(untitled) (Texas Journal of Engineering and Technology, 2024)
Based on research conducted to ensure optimal microclimate parameters in poultry buildings, a plan and sequence of tasks were developed for conducting experiments on processing and cooling the external air parameters supplied to the newly created device. As a result of research on ensuring optimal microclimate parameters in poultry farms, a plan and a sequence of tasks were developed for conducting experiments to process and cool the parameters of external air supplied to the created device. After normalizing the temperature and humidity indicators, modern measuring instruments with high reliability of measurement results were selected to determine the operational efficiency of the equipment. Various outdoor air parameters were adopted to assess the equipment’s performance under different conditions.